Pengaruh E-Service Quality Terhadap Self-Efficacy (Studi Kasus Pengguna Mandiri Online Di Jember, Situbondo, Probolinggo, Bondowoso, Lumajang Dan Banyuwangi) - Verto septiandika; Astutik, Murtias Puji (Jurnal Niara, 2023)
In keeping the business alive in the midst of intense competition, companies need to pay special attention to service quality. Especially in the era of technology, companies are required to be able to adapt and provide services electronically or electronic service quality. E-service Quality is a measuring tool to determine the level of customer satisfaction with a network-based service such as online shopping or product/service delivery. Banking is also affected by the development of information technology, including one of the largest banks in Indonesia, namely Bank Mandiri. Efforts made by Bank Mandiri to innovate in the field of technology are by creating Mandiri Online in 2017. Self-efficacy is a person's ability to complete a lever. The purpose of this study is to find out how the influence of e-service quality on self-efficacy in the use of Mandiri Online in the cities of Jember, Situbondo, Probolinggo, Bondowoso, Lumajang and Banyuwangi. Based on the research conducted, the e-service quality of the Mandiri Online system has a positive influence on the satisfaction of its users. So that this can have an effect on increasing one's self-efficacy or confidence to participate in using Mandiri Online services. Keywords: E-service quality, self-efficacy, Mandiri Online